The Impact Of The Theory Of Formative Analysis On The Construction Of Contemporary Arabic Dictionaries/ أثر نظرية التحليل التكويني في بناء المعاجم العربية المعاصرة - Al-Kalbi, Bader Ayed (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This study links modern semantic theories and contemporary lexicography in the Arabic language by demonstrating the impact of the theory of formative analysis on the dictionary of the modern Arabic language and the role of this theory in solving lexical problems and clarifying meanings and contexts. The study relied on a descriptive analytical approach to tracking, describing, and analyzing linguistic phenomena to reach the intended findings. The study has revealed several conclusions, including the importance of the theory of formative analysis in terms of its applications. It uses the distinction of the contemporary Arabic language dictionary in using modern semantic theories and benefiting from them. Explaining the features of the impact of the theory of formative analysis in solving lexical problems, including the issue of defining known meanings, the problem of defining abstract meanings, and the problem of redefining in dictionary-making, and examining cases of the role of the theory of formative analysis in clarifying and explaining meanings, and examining their derivations and contexts.